Transcriptome Analysis Reveals That Alfalfa Promotes Rumen Development Through Enhanced Metabolic Processes and Calcium Transduction in Hu Lambs - Yang, Bin; Chen, Hongwei; Cao, Jiawen; He, Bo; Wang, Shanshan; Luo, Yang; Wang, Jiakun (Frontiers in Genetics, 2019)
A healthy gut is very important for young animal development. The rumen of ruminants expands in size with the colonization of microbiota by two months of age. This process is promoted by alfalfa intervention. To elucidate the mechanism of this promotion, we performed transcriptomic analyses using a cohort of 23 lambs to evaluate the effects of starter diets plus alfalfa on the development of the rumen wall from the pre- to the postweaning period. The quantitative PCR analyses were used to validate selected genes that were differentially expressed in the transcriptome mapping. We found that several metabolic processes associated with rumen tissue development were affected by solid feed intake with genes linked to the calcium signaling transduction pathway and the metabolism of pteridine-containing compounds and homocysteine metabolic process being upregulated in the group with alfalfa intervention. The results suggest that the pteridine-containing compounds and calcium signaling are targets for precise regulation of rumen development.